2014
DOI: 10.1055/s-0034-1379363
|View full text |Cite
|
Sign up to set email alerts
|

Ground- and Excited-State Quinones: Perspectives in Organocatalysis and Visible-Light Photocatalysis

Abstract: Quinone organocatalysis is an emerging area, and this report highlights some recently developed thermal and photocatalytic reactions, with particular emphasis on photooxygenation reactions. Further, it is discussed how the orthogonal ground-and excitedstate reactivities of quinones can be utilized for the development of tandem catalytic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…A less explored but promising approach that can complement the AO process is to use the excited-state properties of anthraquinones (or other chromophores) to catalyze the production of H 2 O 2 from air. Anthraquinones are highly useful in organic photoredox catalysis, , having been used to initiate the photooxidation of benzylic substituents, , 1,3-diketones, alcohols, and to epoxidize enones . They have also successfully been employed in arene hydrodehalogenations .…”
Section: Introductionmentioning
confidence: 99%
“…A less explored but promising approach that can complement the AO process is to use the excited-state properties of anthraquinones (or other chromophores) to catalyze the production of H 2 O 2 from air. Anthraquinones are highly useful in organic photoredox catalysis, , having been used to initiate the photooxidation of benzylic substituents, , 1,3-diketones, alcohols, and to epoxidize enones . They have also successfully been employed in arene hydrodehalogenations .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, the photoredox catalytic process has been proven to be one of the most powerful tools, providing promising alternatives to achieve novel transformations. Compared to transition-metal-based photocatalysts, there is a special interest in the organophotocatalysts , because they contribute to the development of green and novel synthetic methods. Meanwhile, anthraquinones (AQs) comprise a family of organophotocatalysts that, due to their great capacity to easily reach long-lived excited (n-π*) triplet states, possess radical-type properties that allow for carrying out a wide diversity of photoinduced chemical transformations, such as single electron transfer (SET), hydrogen atom transfer (HAT), as well as [2 + 2] cycloaddition to produce the corresponding oxetans (Scheme a) . However, AQs that are substituted with a group such as −OH or −NH 2 at a location that allows the formation of an intramolecular hydrogen bond are accepted as poor photosensitizers.…”
mentioning
confidence: 99%
“… 13 This is in contrast with the relatively low number of studies reported where quinones were studied as photocatalysts, even though their excited states are known to exhibit high oxidation potentials. 14 An exception to this is anthraquinone as a photo-oxidant. Besides being reported as a competent electron and hydrogen atom acceptor, it also often acts as a catalyst to produce reactive oxygen species.…”
mentioning
confidence: 99%
“… 15 For the current study, the latter feature would be unsuitable, as our interest was to discover catalysts able to oxidize the imine substrates via either single electron transfer (SET) or hydrogen atom transfer (HAT) and be regenerated by atmospheric oxygen afterward. 6b , 14 In this frame, visible-light-excited 9,10-phenanthrenequinone (PQ) raised our attention as a potential photocatalyst.…”
mentioning
confidence: 99%